Quantitative assessment of a pediatric nociception monitor in children under sevoflurane anesthesia. Issue 9 (2nd June 2022) - Lebrun, Sebastien; Boccara, Johanna; Cailliau, Emeline; Herbet, Mathilde; Tavernier, Benoit; Constant, Isabelle; Sabourdin, Nada
Abstract : Introduction: Intraoperative monitoring of nociception has recently made substantial progress in adult anesthesia. In contrast, pediatric data are scarce. Newborn-Infant Parasympathetic Evaluation (NIPE index, Mdoloris Medical Systems, Loos, France) is the first nociception index specifically designed for young children. It is a dimensionless index comprised between 0 and 100. Two previous studies suggested that NIPE could indeed 'detect' nociception in anesthetized children. The objective of our study was to investigate if NIPE allowed to detect and to provide a quantitative assessment of nociception in children. Methods: Children were anesthetized with sevoflurane, and received a bolus of alfentanil (10 µg/kg before intubation). Before surgical incision, each participant received three tetanic stimulations (5 s, 100 Hertz) with a 5 min interval, in a randomized order: 10, 30 and 60 milliamps. NIPE and heart rate variations were assessed after each stimulation. Results: Thirty children (2.4±1.6 years) were included. Mean delay between alfentanil and the first stimulation was 19±4 min. Mean baseline NIPE was 75±10. NIPE variation after the stimulations was significant at 10, 30 and 60 mA (linear mixed regression model, p<0.001). The intensity of stimulation significantly influenced the amplitude of NIPE variation (linear mixed regression model p<0.001), but had no statistically significant effect on heart rate variation (p=0.52). Discussion: NIPE might allow a quantitative assessment of nociception in young children in these anesthetic conditions. This study provides a basis for future research investigating the potential benefits of NIPE-guided intraoperative analgesia in pediatric anesthesia. Trial registration number: NCT04381637 .